LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING DALAM MENINGKATKAN SELF ESTEEM SISWA KELAS VII SMPN 16 CIMAHI - Sifa Mandiri; Wahyu Hidayat; Williya Novianty (IKIP Siliwangi, 2024)
The purpose of this research is to determine: the effectiveness of group guidance using role-playing techniques in enhancing students' self-esteem, and the challenges faced in implementing group guidance services using role-playing techniques to improve self-esteem. The research method used is a mixed method with an explanatory sequential design. Quantitative data was collected through questionnaires (pretest and posttest) and analyzed using the t-test, while qualitative data was collected through observations and interviews and analyzed using data reduction techniques. The research was conducted at SMPN 16 Cimahi, and the subjects of the study were 8 seventh-grade students. The results of the quantitative data indicate an improvement in students' self-esteem through the implementation of group guidance using role-playing techniques with a significance value (2-tailed) of 0.000 < 0.05. From the qualitative data, it is shown that the challenges faced by students come from themselves and others (group members), such as difficulty in understanding and performing the assigned roles, accompanied by feelings of embarrassment or discomfort when role-playing in front of their peers.